Agricultural suitability and fertility in occidental piedmont of Calchaquíes Summits (Tucumán, Argentina) - Sampietro Vattuone, Maria Marta (2014)
Our study area is located in the piedmont of Calchaquíes Summits (Tucumán Province, Northwest Argentina). The objectives of this paper are to improve the knowledge of Pre-Hispanic agricultural practices on landscape and soils, and to provide new knowledge about land fertility of agricultural areas, taking into account the environmental settings. Physical and chemical features, such as structure, texture, pH, calcium, organic and inorganic phosphorus, and available copper, manganese, and iron were taken into account. After photointerpretation and field surveys, two agricultural terraced geomorphological units were sampled. Samples were made in comparable off-site locations and the archaeological sites. After Principal Component Analysis, physicochemical analysis showed that texture is the most significant difference between the two archaeological sites. Agricultural practices introduced high chemical variations, despite the substantial differences between agricultural and off-site profiles. This is the first approach of this nature in Northwest Argentina.